2013
DOI: 10.3201/eid1908.121535
|View full text |Cite
|
Sign up to set email alerts
|

Duck Liver–associated Outbreak of Campylobacteriosis among Humans, United Kingdom, 2011

Abstract: Campylobacter­ spp.–related gastroenteritis in diners at a catering college restaurant was associated with consumption of duck liver pâté. Population genetic analysis indicated that isolates from duck samples were typical of isolates from farmed poultry. Campylobacter spp. contamination of duck liver may present a hazard similar to the increasingly recognized contamination of chicken liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…Several persons attending a wedding reception on 26 May 2012 became ill. An outbreak investigation identified chicken liver pâté as the suspected source of the infection. Several Campylobacter outbreaks associated with consumption of poultry liver pâté have been described especially in the UK (Abid et al., ; Edwards et al., ; Farmer et al., ; Forbes et al., ; Inns et al., ; Little et al., ; O'Leary et al., ; Wensley and Coole, ; Young et al., ) but also in other countries such as Australia (Merritt et al., ; Parry et al., ) and USA (Centers for Disease & Prevention, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several persons attending a wedding reception on 26 May 2012 became ill. An outbreak investigation identified chicken liver pâté as the suspected source of the infection. Several Campylobacter outbreaks associated with consumption of poultry liver pâté have been described especially in the UK (Abid et al., ; Edwards et al., ; Farmer et al., ; Forbes et al., ; Inns et al., ; Little et al., ; O'Leary et al., ; Wensley and Coole, ; Young et al., ) but also in other countries such as Australia (Merritt et al., ; Parry et al., ) and USA (Centers for Disease & Prevention, ).…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence of an increased risk of Campylobacter infection in humans associated with ducks (10). A study in the United Kingdom found that duck meat was implicated in 2% of campylobacteriosis outbreaks (11), and a large outbreak of campylobacteriosis was derived from duck products in the United Kingdom (12). Previous surveys indicated high prevalences of Campylobacter in domestic ducks and duck meat (11,13).…”
mentioning
confidence: 99%
“…It is already apparent that studies of microbial pathogenicity at the molecular level have made substantial contributions to our understanding of the epidemiology, clinical manifestations, diagnosis, treatment, and immunoprophylaxis of infectious diseases. Infectious disease epidemiology hinges on a clear definition of the clinical problem under study and, moreover, precise identification of the etiologic agent [3][4][5][6]. Molecular techniques provide for the sensitive and specific detection of putative pathogens and supply a means for establishing relationships among multiple isolates of the same species.…”
Section: Pathogen Detection Pathogen Discovery and Genomic Profilingmentioning
confidence: 99%
“…Molecular techniques have been used in other epidemiologic investigations to study transmission mechanisms and the role of avirulent microbial variants in the spread of disease [3][4][5][6][7]. Molecular strain typing data some-times provide the only clue that a group of cases are related, that is, that an outbreak of disease has occurred.…”
Section: Pathogen Detection Pathogen Discovery and Genomic Profilingmentioning
confidence: 99%
See 1 more Smart Citation